Development of Interactive Learning Android Application for Basic Mathematical Concepts - Hamzah, Norhasyimah; Zamri, Nur Natasya Najwa; Ariffin, Arihasnida Ariffin; Zakaria, Normah; Rubani, Siti Nur Kamariah (Research and Innovation in Technical and Vocational Education and Training, 2022)
This project aims to design and develop interactive learning android application Mathematical concepts. The development of this interactive android application is to assist students in learning the basics of Mathematics easily. The model used in this product development is the ADDIE design model which requires five of analysis, design, development, implementation, and evaluation. The analysis phase is carried out through observation to identify problems. For the design phase, the developer produces a storyboard and determines the software to be used. In the development phase, the developer collects and produces multimedia elements such as text, video, audio, animation, and graphics. For the implementation phase, they develop a prototype by using all the materials that have been produced according to the storyboard. The evaluation was conducted by three (3) experts in a creative multimedia field from the Faculty of Technical and Vocational Education, University Tun Hussein Onn Malaysia, and experts in Mathematical content. The instrument of study used is the expert checklist form. Data analysis used frequency methods. The results of the study found that three (3) experts gave positive feedback on this developed product. The development of this interactive learning android application can help teachers in carrying out the teaching and learning process and be used as a guide by students in practicing the basic Mathematical namely addition, subtraction, multiplication, and division operations.